Use of Classical Adsorption Theory to Understand the Dynamic Filtration of Volatile Toxicants in Cigarette Smoke by Active Carbons - Peter J. Branton; Kevin G. McAdam; Martin G. Duke; Chuan Liu; Maria Curle; Michele Mola; Christopher J. Proctor; Robert H. Bradley (Adsorption Science & Technology)
The ability of two very different active carbons, a polymer-derived carbon (with ultramicropores and supermicropores, and a large volume of “transport” pores) and a coconut shell-derived carbon (predominantly ultramicroporous), to reduce the levels of volatile toxicants in cigarette smoke has been measured and compared. The polymer-derived carbon was found to be approximately twice as effective in removing the majority of measured smoke vapour-phase toxicants compared to the coconut shell-derived carbon in three different cigarette formats and with two different smoking regimes. Single-component dynamic breakthrough experiments were conducted with benzene, acrylonitrile and 2-butanone at 298 K for beds of each carbon under dry (0% RH) and wet (60% RH) conditions. Longer breakthrough times were found with the polymer-derived carbon, and breakthrough times recorded under wet conditions were found to be up to 20% shorter than those obtained under dry conditions. Correlations between micropore volume, dynamic adsorption volume and filter bed breakthrough time have been demonstrated.